2019
DOI: 10.1111/eff.12487
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the behavioural thermoregulation response to heat stress by Atlantic salmon parr (Salmo salar) in two rivers

Abstract: Climate change is expected to increase the frequency and magnitude of extreme thermal events in rivers. The Little Southwest Miramichi River (LSWM) and the Ouelle River (OR) are two Atlantic salmon (Salmo salar) rivers located in eastern Canada, where in recent years, water temperatures have exceeded known thermal limits (~23°C). Once temperature surpasses this threshold, juvenile salmon exploit thermal heterogeneity to behaviourally thermoregulate, forming aggregations in coolwater refuges. This study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 65 publications
(94 reference statements)
3
54
0
Order By: Relevance
“…Atlantic salmon parr were not limited fully to cold‐water refugia until ambient river temperature exceeded 27°C, an observation consistent with their higher temperature tolerance compared to brook trout. During five sampling days (non‐consecutive) when the ambient river temperature exceeded 25°C, small aggregations of salmon parr (3–6 fish) were observed on the fringe of, and within, cold‐water anomalies and all parr were within the cold‐water plume when the ambient river temperature reached 27°C, as also reported by Corey et al (). Corey, Linnansaari, Cunjak, and Currie () found repeated exposure to extreme temperature lowers the thermal threshold in salmon parr.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Atlantic salmon parr were not limited fully to cold‐water refugia until ambient river temperature exceeded 27°C, an observation consistent with their higher temperature tolerance compared to brook trout. During five sampling days (non‐consecutive) when the ambient river temperature exceeded 25°C, small aggregations of salmon parr (3–6 fish) were observed on the fringe of, and within, cold‐water anomalies and all parr were within the cold‐water plume when the ambient river temperature reached 27°C, as also reported by Corey et al (). Corey, Linnansaari, Cunjak, and Currie () found repeated exposure to extreme temperature lowers the thermal threshold in salmon parr.…”
Section: Discussionsupporting
confidence: 83%
“…It is possible that salmon parr we observed were exposed to multiple temperature stress events and thus may have begun to aggregate at 25°C (Corey et al, ). Our observations and conclusions regarding temperature triggers of behaviours cannot unravel the effects of the thermal regime exposures the fish have experienced in‐year and over many years (Corey et al, ; Corey et al, ), but the observed salmon parr behaviour suggests that temperature sensitivities and response triggers are being affected in this northern, temperate river.…”
Section: Discussionmentioning
confidence: 67%
“…However, smaller streams that are groundwater dominated can remain ice free to varying degrees (Figure ; Cunjak et al, ). In summer, river temperatures can exceed 30°C in the Miramichi (see Corey et al, ), whereas in winter, river temperatures are typically not observed to be much lower than 0°C (Cunjak & Caissie, ). Groundwater thermal regimes in the Miramichi vary with depth and display a lagging behaviour in relation to seasonal air temperature fluxes.…”
Section: Methodsmentioning
confidence: 99%
“…Climate change is projected to have broad‐scale implications for river ecology including increasing pressure on native coldwater species (Corey et al, 2019; Wilbur et al, 2020) and highlights the importance of thermal refugia in the age of climate warming in northern temperate and boreal regions of the world. The models generated herein will prove useful in preliminary efforts by fisheries and land use management to (a) identify and (b) protect and conserve critical coldwater habitat in these northern temperate settings.…”
Section: Resultsmentioning
confidence: 99%
“…During high temperature events, salmonids will seek out thermal refugia, that is, colder water, to mitigate physiological stress (Corey et al, 2017; Wilbur et al, 2020). These refugia are most often groundwater features (Curry & Devito, 1996) and can vary from fine‐scale, localized bank seeps (Wilbur, 2012) and hyporheic upwellings (Krause et al, 2011), to broader‐scale, tributary inflows (Corey et al, 2019). At the southern extent of Atlantic Salmon and Brook Trout ranges, increasing river temperature associated with climate change is beginning to have negative effects on both species (Corey et al, 2019; Dugdale et al, 2016).…”
Section: Introductionmentioning
confidence: 99%